2-18 GHz conformal low-profile log-periodic array on a cylindrical conductor - Chen, Qiaoyu (2020)
This paper presents a conformal log-periodic array covering an ultra-wideband of 2-18 GHz. It employs monopoles of different heights for the high band, top-hat monopoles for the middle band, and folded top-hat monopoles for the low band. The top hats help to achieve a low profile of the monopoles while the folding is to maintain a good input resistance at the low band. A meandering microstrip line on the bottom is used to feed the array. The proposed antenna is mounted on a conducting cylindrical surface with all the top hats conformal and aligned to the outline of the cylinder. A prototype is fabricated and tested. Measured results show that an impedance bandwidth from 2 to 18.3 GHz (9.15:1) for VSWR < 2 is obtained. Over the same band, the measured gain is better than 7.2 dBi. The antenna has a very low profile of 0.053 λL at the lowest operating frequency, which should be useful in many communication systems such as missile and airborne applications.